Figurative language in the olfactory domain across Chinese and English: Examples of chòu (臭) and foul/smelly /stinking - Zhao, Xuan (ExELL, 2025)
Conventionally, smell has been regarded as a relatively ineffable percept and concept. However, the personal experience of using the olfactory Chinese word chòu (臭, 'smelly') makes me think that the word is not so ineffable in China as people often use it daily. To verify the hypothesis that the Chinese character chòu (臭) has distinctive figurative sense and collocation patterns compared with English terms like foul, smelly, or stinking, the study used corpus-linguistic data to identify the salience, frequency, and collocation of olfactory words in Chinese and English. The study shows that the psychological similarity between bad smell and negative mental states is very salient in both languages. Nevertheless, the construal of the subjective feelings conveyed through these olfactory words is subject to the specific context and the speaker's intention.